Automorphism bases for the recursively enumerable degrees: in memory of S. Barry Cooper (1943-2015) - Ambos-Spies, Klaus (Computability, 2018)
We give various examples of automorphism bases for the recursively enumerable (r.e.) degrees. In particular, we show that any nontrivial initial segment of the r.e. degrees is an automorphism base.